Wavelength filter using twin one‐dimensional photonic crystal cavity silicon waveguides. Issue 2 (1st January 2019) - Okayama, H.; Onawa, Y.; Shimura, D.; Takahashi, H.; Yaegashi, H.; Sasaki, H.
Abstract : A wavelength filter using a pair of one‐dimensional photonic crystal (1D‐PhC) waveguides incorporating cavity sections for one‐directional output is reported. The small number of holes for 1D‐PhC is used to attain distinct transmission peaks in the stop band. Two cavity sections are used to obtain peak with steep slope and widened top. The three‐dimensional finite difference time domain simulation results agree with the experimental result.